Physical development, the level of physical and technical preparedness of 14 - 15 year old young weightlifters of different weight categories groups - Iu.A. Lutovinov; V.D. Martin; V.G. Oleshko; V.N. Lisenko; K.V. Tkachenko (Physical Education of Students, 2014)
Purpose : explore physical development, the level of physical and technical preparedness of young weightlifters of different weight categories groups. Material : the study involved 36 athletes. Athletes age 14-15 years. Results : present physical development, the level of physical and technical preparedness of athletes who are preparing for the championship of Ukraine. Found that indicators body length athletes tend to increase with increasing weight category groups - by 15,0% (p